Руслан и Людмила: [поэма : для среднего школьного возраста] / А. С. Пушкин - Пушкин Александр Сергеевич (Книги - мои друзья, 2015)
Экземпляры: ф.4 (20160713) / Инвентарный номер: 2694 / Цена: / Сис.шифр: 84(2Рос=Рус)1-5 / Авт.знак: П 91 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)1-5